A study on the profile and sexual behaviour of patients in an ICTC Centre in a District Hospital in North India - Neerja Puri; Ashutosh Talwar; MRS Monika (Our Dermatology Online, 2014)
Introduction: Integrated counseling and testing (ICTC) for HIV is a cost-effective intervention in preventing the spread of HIV transmission and is an integral part of HIV prevention program, which provides an opportunity to learn and accept the HIV status in a comfortable, convenient, and confidential manner. Material and Methods: A retrospective study of 3600 attendees visiting the ICTC centre from April 2010 to April 2011was undertaken. The study included 3600 attendees who came either voluntarily or referred by various department of this institute. Dominant reason for visiting ICTC was the history/presence of high risk behavior (HRB). Results: 60% indulged in heterosexual route; other HRB including men having sex with men or MSM were 5% and injecting drug users or IDU) were 15%. There were more positive among males, 21-40 years of age group, those living singly, unmarried, divorcee, widow(er) and separated. Similarly positives were more amongst illiterates, less educated and those engaged in unskilled and semi skilled jobs. Adolescent students (>14 years) accounted for one-fifth of the total positives. Direct walk in clients were more positive compared to those referred by doctors. Overall sero positivity was 4.8%; high in males, 21-40 years age, unmarried and divorcee etc. Conclusions: Sero prevalence decreased with improvement in education and also with improvement in job nature. It was also high in those living alone compared to those staying with their family.